2021
DOI: 10.1126/sciadv.abg2099
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Wnt/PCP signaling through p97/VCP-KBTBD7–mediated Vangl ubiquitination and endoplasmic reticulum–associated degradation

Abstract: The four-pass transmembrane proteins Vangl1 and Vangl2 are dedicated core components of Wnt/planar cell polarity (Wnt/PCP) signaling that critically regulate polarized cell behaviors in many morphological and physiological processes. Here, we found that the abundance of Vangl proteins is tightly controlled by the ubiquitin-proteasome system through endoplasmic reticulum–associated degradation (ERAD). The key ERAD component p97/VCP directly binds to Vangl at a highly conserved VCP-interacting motif and recruits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 83 publications
(146 reference statements)
0
28
0
Order By: Relevance
“…Our results suggest that the substrate-ubiquitinating Mib1 RING-finger domains are required for PCP. As Ubiquitin-dependent membrane trafficking is important for PCP ( Butler and Wallingford, 2017 ; Devenport, 2014 ; Feng et al, 2021 ), we set out to determine whether Mib1 controls CE by regulating the trafficking of a PCP pathway component.…”
Section: Resultsmentioning
confidence: 99%
“…Our results suggest that the substrate-ubiquitinating Mib1 RING-finger domains are required for PCP. As Ubiquitin-dependent membrane trafficking is important for PCP ( Butler and Wallingford, 2017 ; Devenport, 2014 ; Feng et al, 2021 ), we set out to determine whether Mib1 controls CE by regulating the trafficking of a PCP pathway component.…”
Section: Resultsmentioning
confidence: 99%
“…Both Vangls have conserved basolateral-sorting motifs (YXXF) critical for the recruitment of Vangl into transport vesicles, and proper cell membrane localization of Vangl ( Guo et al, 2013 ; Iliescu and Gros, 2014 ). More recently, a p97/VCP-interacting motif (VIM motif) was identified in the C-terminal of Vangl2 that is required for direct interactions between Vangl2 and p97/VCP, a chaperone-related ATPase, which is critical for ubiquitination and degradation of Vangl through the endoplasmic reticulum-associated degradation (ERAD) pathway ( Feng et al, 2021 ). The C-terminal tail of Vangl also contains a Prickle binding domain (PkBD) that facilitates interactions between Vangl and the cytosolic effector Pk ( Nagaoka et al, 2019 ).…”
Section: Vangl Structure Promotes Assembly Of Diverse Binding Partnersmentioning
confidence: 99%
“…A recent study identified a novel post-translational mechanism for regulating Vangl protein levels. Feng et al (2021) determined that Vangl2 proteins are basally phosphorylated in the ER prior to being transported to the cell membrane. Vangl2 proteins lacking basal phosphorylation are marked for endoplasmic reticulum-associated protein degradation (ERAD).…”
Section: Proper Localization Of Vangl Is Critical For Functionmentioning
confidence: 99%
“…Previous studies have revealed the extensive role of VCP in SG clearance. Disease-related VCP mutants significantly impair SG disassembly and lead to elevated oxidative stress in an animal model. ,, Considering that VCP is an important node in the endoplasmic reticulum-associated degradation (ERAD) pathway , and that the regulation of cellular condensate dynamics is tightly related to ER membrane contact sites, an intriguing hypothesis is that the clearance of intracellular condensates, including SGs, may share some common pathways with the ERAD system. In addition, ALS-related mutations can disrupt the autophagy-mediated disassembly of “chronic SGs”.…”
Section: Deficiency In the Clearance Of Stress-induced Condensates Ex...mentioning
confidence: 99%